Electromagnetic Shielding Characteristics of Eco-Friendly Foamed Concrete Wall - Sung-Sil Cho; Jin-Man Kim; Ic-Pyo Hong (International Journal of Antennas and Propagation)
The electromagnetic shielding characteristics according to the material composition of foamed concrete, which was manufactured to reduce environmental pollution and to economically apply it in actual building walls, were researched herein. Industrial by-products such as ladle furnace slag (LFS), gypsum, and blast furnace slag (BFS) were added to manufacture foamed concrete with enhanced functionalities such as lightweight, heat insulation, and sound insulation. The electrical characteristics such as permittivity and loss tangent according to the foam and BFS content were calculated and measured. Free space measurement was used to measure the electromagnetic shielding characteristics of the actually manufactured foamed concrete. It was confirmed that electromagnetic signals were better blocked when the foam content was low and the BFS content was high in the measured frequency bands (1–8 GHz) and that approximately 90% of the electromagnetic signals were blocked over 4 GHz.